PENGARUH METODE MENDONGENG DENGAN BANTUAN BONEKA TANGAN TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SDI KEBUNREJO - Nurul Fatimah; Azizatul Layali; Eka Ramiati (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
This study aims to find out whether the storytelling method with the help of hand puppets has an effect on the speaking skills of grade IV students of SDI Kebunrejo for the 2023/2024 Academic Year. This study uses a quantitative approach with the type of experiment, the sample in this study is all grade IV of SDI Kebunrejo which totals 29 students. The variables of this study consist of an independent variable, namely the storytelling method with the help of hand puppets and a bound variable, namely speaking skills. Meanwhile, data collection uses observation and research instruments to search for influence data. storytelling method (X) towards the development of speaking skills (Y). From the results of the T test, the test showed that the fourth grade students of SDI Kebunrejo when the application of the storytelling method without using hand puppets to speaking skills obtained a result of 39.34 after being given the application of the storytelling method with the help of hand puppets, the result was 43.21 experienced an increase of 3.87 this is evidenced by the results of the T test, tcount -8.661 with df 28 is 0.3862, so that the tcount number is greater than the ttable, then it can be said that H0 is rejected and Ha is accepted. Meanwhile, if you look at the significant value, 0.00≤0.05 is obtained, so it can be said that H0 is rejected and the research hypothesis is accepted. Which means that there is an effect of the application of the storytelling method with the help of hand puppets on the speaking skills of grade IV students in Indonesian language lessons with storytelling materials at SDI kebunrejo Genteng Banyuwangi for the 2023/2024 school year, so that H0 is rejected.